(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The research paper describes a pre-experimental study that aimed to assess the knowledge and effectiveness of a self-instructional module on foot care among diabetes patients in selected hospitals in Bhopal. The study design involved pre- and post-intervention assessments, without a control group. The study included a sample of diabetes patients from three hospitals in Bhopal, and the sample size was determined based on convenience sampling. The patients’ knowledge of foot care was assessed using a questionnaire before and after the intervention, which consisted of a self-instructional module on foot care. The self-instructional module covered various aspects of foot care, including proper foot hygiene, regular foot inspections, and strategies for preventing foot injuries and infections. The module was developed by the researchers based on current guidelines for diabetes management. The results of the study showed that the self-instructional module was effective in improving patients’ knowledge of foot care. The implications of the study suggest that self-instructional modules on foot care may be an effective strategy for improving diabetes self-management. However, the study’s limitations, such as the small sample size and lack of a control group, highlight the need for further research to confirm the effectiveness of educational interventions on foot care among diabetes patients. Overall, the study emphasizes the importance of patient education and support to prevent foot complications and other diabetes-related health problems.